Bibliometric analysis highlighting the role of women in addressing climate change challenges and achieving sustainable development goals for greener future - Rezk, Hegazy; Sayed, Enas Taha (Institute of Advanced Engineering and Science, 2024)
Fossil fuel consumption increased quickly, contributing to climate change that is evident in unusual flooding and draughts, and global warming. Over the past ten years, women's involvement in society has grown dramatically, and they succeeded in playing a noticeable role in reducing climate change. A bibliometric analysis of data from the last ten years has been carried out to examine the role of women in addressing the climate change. The analysis's findings discussed the relevant to the sustainable development goals (SDGs), particularly SDG 7 and SDG 13. The results considered contributions made by women in the various sectors while taking geographic dispersion into account. The bibliometric analysis delves into topics including women's leadership in environmental groups, their involvement in policymaking, their contributions to sustainable development projects, and the influence of gender diversity on attempts to mitigate climate change. This study's results highlight how women have influenced policies and actions related to climate change, point out areas of research deficiency and recommendations on how to increase role of the women in addressing the climate change and achieving sustainability. To achieve more successful results, this initiative aims to highlight the significance of gender equality and encourage inclusivity in climate change decision-making processes.